The Relationship Between Family Support and Quality of Life of Hemodialysis Patients At RSU Royal Prima Medan - Cristiani Harefa; Sri Purjianti; Feryaman Dachi; Maya Khairiyah; Johannes Siahaan; Karmila Br Kaban (Universitas Malahayati Lampung, 2023)
ABSTRACT Hemodialysis is a form of treatment for patients with temporary or permanent loss of kidney function due to chronic kidney disease. Family support is a factor that can influence hemodialysis therapy in patients. One of the factors that support the success of nursing work is the involvement of the patient's family. Good patient quality of life is an important aspect in the provision of comprehensive medical services. To see the relationship between family support and quality of life in hemodialysis patients. This type of research uses an analytic survey with a cross-sectional design. The population includes all hemodialysis patients. The sampling technique uses random sampling, so that the sample is 32 people. The results of the study prove that the majority of family support for hemodialysis patients at RSU Royal Prima has good family support. The majority of the quality of life for hemodialysis patients at RSU Royal Prima is very good. There is a relationship between family support and quality of life in hemodialysis patients at RSU Royal Prima. It is hoped that the family should provide support so that the respondent can accept his condition and can carry out hemodialysis treatment regularly. It is hoped that research sites can provide better health service facilities and provide health education regarding family support with the quality of life of hemodialysis patients. Future researchers are expected to be able to examine other diseases with the same variables. Keywords: Family Support, Quality of Life, Hemodialysis ABSTRAK Hemodialisis adalah bentuk perawatan untuk pasien dengan kehilangan fungsi ginjal sementara atau selamanya karena penyakit ginjal kronis. Dukungan keluarga adalah faktor yang bisa mempengaruhi terapi hemodialisa pada pasien. Salah satunya faktor yang mendukung keberhasilan kerja keperawatan adalah keterlibatan keluarga pasien. Kualitas hidup pasien yang baik ialah aspek penting dalam penyediaan layanan medis yang komprehensif. Untuk melihat hubungan antara dukungan keluarga dengan kualitas hidup pada pasien hemodialisis. Jenis penelitian memakai survei analitik dengan desain cross sectional. Populasi mencakup semua pasien hemodialisis. Teknik penarikan sampel memakai random sampling, sehingga sampel berjumlah 32 orang. Hasil penelitian membuktikan dukungan keluarga pada pasien hemodialisa di RSU Royal Prima mayoritas dukungan keluarga baik. Kualitas hidup pada pasien hemodialisa di RSU Royal Prima mayoritas kualitas hidup sangat baik. Ada hubungan dukungan keluarga dengan kualitas hidup pada pasien hemodialisa di RSU Royal Prima. Diharapkan keluarga sebaiknya memberikan dukungan sehingga responden bisa terima kondisinya serta bisa melakukan pengobatan hemodialisa secara rutin. Diharapkan tempat penelitian bisa menyediakan fasilitas pelayanan kesehatan lebih baik lagi dan memberi pendidikan kesehatan mengenai dukungan keluarga dengan kualitas hidup pasien hemodialisa. Peneliti selanjutnya diharapkan bisa meneliti penyakit lain dengan variabel yang sama. Kata Kunci: Dukungan Keluarga, Kualitas Hidup, Hemodialisa